Three-phase quasi-Z source inverters with regulated multiple AC outputs for microgrid applications and three-phase residential load - Sonkar S.P.; Lal V.N.; Singh R.K. (My University, 2025)
In this study, two 3-f quasi-Z source inverters (qZSIs) with multiple ac outputs are proposed. The proposed topologies are developed from qZSI to obtain parallel mode and series mode 3-f multi-output inverters. In parallel mode, the topology yields n-number of parallel ac outputs with different voltages and currents for different load conditions. For series mode, topology yields n-number of series ac outputs with same voltages and same load currents. Unlike voltage source derived multi-output inverters, the proposed inverters have all inherent properties of qZSI, like shoot-through protection and both buck- boost operations. For generating switching signals in these inverters, sinusoidal pulse width modulation with constant frequency shoot-through scheme is used. The proposed topologies fulfil more than one load demand at a time without any extra adaptor or regulator. The proposed inverters can be used for simultaneous multiple dc/ac power conversion for three-phase microgrid applications and three-phase residential loads. In this work, the proposed topologies with closed-loop control have been implemented for two inverter units, which is capable of supplying two ac outputs simultaneously. The mathematical modelling of the proposed topologies is carried out for performance analysis. The experimental results of 240 W lab prototypes have been presented to validate the proposed three-phase multi-output qZSIs. © 2020 Institution of Engineering and Technology. All rights reserved.